Isolasi, Karakterisasi dan Uji Aktivitas Biologi Asam Kojat dari Fermentasi Cair Aspergillus Flavus LS03 - Hani Mulyani; Rizna T D; Megawati Megawati; Sofa Fajriah (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Aspergillus flavus LS03 is a type of fungus isolated from rhizosphere soil in West Lombok, which showed potential as an α-glucosidase inhibitor and free radical scavenger in the early stages of screening activity. This study aimed to identify and characterize secondary metabolite as antidiabetic and antioxidants from A. flavus LS03 fungus grown on liquid medium of potato broth (PDB). The testing of antidiabetic activity is based on the inhibition of the α-glucosidase enzyme while the antioxidant is based on the ability to reduce DPPH free radicals. The result of separation and purification was obtained by active isolate (1) which was identified as 5-hydroxy-2- (hydroxymethyl) -1.4-piran (kojic acid) based on spectroscopic data. Kojic acid (1) shows strong potential as an α-glucosidase enzyme inhibitor and free radical DPPH with IC50 values of 35.34 and 149.9 μg / mL, respectively.